Digitalisasi Profil dan Informasi Sekolah Global Mandiri Patrol Melalui Pembuatan Website - Ahmad Turmudi Zy; Agung Nugroho; Sunita Dasman; Donny Maulana; Isarianto Isarianto (Apik Cahaya Ilmu, 2025)
Global Mandiri Patrol School, a private educational institution located in Indramayu, West Java, faces challenges in disseminating information to students, parents, and the wider community due to the absence of official digital information media. This research aims to implement a Content Management System (CMS)-based school website to support the digital transformation of educational institutions. The community service method is designed participatively through five stages: (1) program socialization, (2) teacher and staff training, (3) technology implementation for website development, (4) intensive website management mentoring, and (5) evaluation and sustainability planning. The research results show that the school website has been successfully launched with all planned features, 2–3 staff members have been trained in content management, and sustainability commitment from school leaders and the foundation has been documented. Measurable social impacts include improved information transparency, enhanced school communication efficiency, increased institutional image, and support for school accreditation processes. Regarding partner capacity, this activity has increased digital literacy among school teachers and staff and opened opportunities for sustained innovation. The conclusion of this research is that school website development is an effective strategic step in supporting the digital transformation of educational institutions and improving service quality to the community